2020
DOI: 10.1042/ebc20190092
|View full text |Cite
|
Sign up to set email alerts
|

Druggable binding sites in the multicomponent assemblies that characterise DNA double-strand-break repair through non-homologous end joining

Abstract: Non-homologous end joining (NHEJ) is one of the two principal damage repair pathways for DNA double-strand breaks in cells. In this review, we give a brief overview of the system including a discussion of the effects of deregulation of NHEJ components in carcinogenesis and resistance to cancer therapy. We then discuss the relevance of targeting NHEJ components pharmacologically as a potential cancer therapy and review previous approaches to orthosteric regulation of NHEJ factors. Given the limited success of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…NHEJ has also been implicated in chromothripsis, a mutational phenomenon in cancer that involves the shattering and rearrangement of a chromosome (43). Moreover, several studies have reported that core NHEJ factors are overexpressed in certain tumor tissues (44), and overly active NHEJ is associated with resistance to DSB-inducing chemotherapy and radiotherapy (45). As such, NHEJ components have emerged as drug targets for cancer therapy (45), and DNA-PKcs inhibitors have entered clinical trials (46).…”
Section: Nhej and Human Healthmentioning
confidence: 99%
“…NHEJ has also been implicated in chromothripsis, a mutational phenomenon in cancer that involves the shattering and rearrangement of a chromosome (43). Moreover, several studies have reported that core NHEJ factors are overexpressed in certain tumor tissues (44), and overly active NHEJ is associated with resistance to DSB-inducing chemotherapy and radiotherapy (45). As such, NHEJ components have emerged as drug targets for cancer therapy (45), and DNA-PKcs inhibitors have entered clinical trials (46).…”
Section: Nhej and Human Healthmentioning
confidence: 99%
“…Furthermore, such systems often change over time, providing major challenges to crystallography, and require dissection using novel single-molecule forceps and related techniques [99]. These structures are proving useful in the design of new cancer therapeutics, not only through targeting the DNA-PKcs kinase active site [100], but also at protein-protein interfaces, especially where polypeptide with an intrinsically disorder region folds and binds, such as the binding of the Artemis tail to a site on the DNA-Ligase IV in NHEJ [101,102].…”
Section: Figure 8 (A)mentioning
confidence: 99%
“…Kawale and Sung focused on the proteins and mechanistic function of the homologous recombination (HR) pathway, describing four major stages: DNA end resection, presynaptic filament assembly, DNA strand invasion and repair DNA synthesis (7). Stavridi et al explained the general mechanism of non-homologues end joining (NHEJ) pathway with focus specifically on druggable binding sites, available small molecule compounds and potential future candidates targeting protein-protein interaction interfaces among key NHEJ protein complexes (8).…”
Section: ) Dna Modification and The Chromatin Environmentmentioning
confidence: 99%